Politics of power and hierarchies of citizenship in Angola - Martins, Vasco (Citizenship Studies, 2017)
This article discusses citizenship and belonging with reference to processes of post-war state formation, namely: the MPLA’s political hegemony and the centralisation of power in the presidency. It argues this political arrangement imposes upon individuals an oscillation between different ‘levels’ or hierarchies of citizenship with a tendency towards marginalisation, formally allowing them to access both but under the specific circumstances dictated by the MPLA party state. Without a strong political opposition with a plausible alternative citizenship doctrine and with little incentives to improve the terms of citizenship it provides to the population, the Angolan government constructed a system of interests whereby the MPLA functions as a gatekeeper. Both in control of the state and of the distribution of citizenship, the regime regulates the flow of resources to the bottom through strategies of poverty and dependency, which increase the distance between the state and the population and sponsors the marginalisation of the majority.